Ferromagnetic behaviour of Fe-doped ZnO nanograined films - Straumal, Boris B (Beilstein-Institut, 2013)
The influence of the grain boundary (GB) specific area s(GB) on the appearance of ferromagnetism in Fe-doped ZnO has been analysed. A review of numerous research contributions from the literature on the origin of the ferromagnetic behaviour of Fe-doped ZnO is given. An empirical correlation has been found that the value of the specific grain boundary area s(GB) is the main factor controlling such behaviour. The Fe-doped ZnO becomes ferromagnetic only if it contains enough GBs, i.e., if s(GB) is higher than a certain threshold value s(th) = 5 × 10(4) m(2)/m(3). It corresponds to the effective grain size of about 40 μm assuming a full, dense material and equiaxial grains. Magnetic properties of ZnO dense nanograined thin films doped with iron (0 to 40 atom %) have been investigated. The films were deposited by using the wet chemistry “liquid ceramics” method. The samples demonstrate ferromagnetic behaviour with J(s) up to 0.10 emu/g (0.025 μ(B)/f.u.ZnO) and coercivity H(c) ≈ 0.03 T. Saturation magnetisation depends nonmonotonically on the Fe concentration. The dependence on Fe content can be explained by the changes in the structure and contiguity of a ferromagnetic “grain boundary foam” responsible for the magnetic properties of pure and doped ZnO.